What to expect from a third step in treatment resistant depression: A prospective open study on escitalopram. (3rd October 2015) - Souery, Daniel; Calati, Raffaella; Papageorgiou, Konstantinos; Juven-Wetzler, Alzbeta; Gailledreau, Joël; Modavi, David; Sentissi, Othman; Pitchot, William; Papadimitriou, George N.; Dikeos, Dimitris; Montgomery, Stuart; Kasper, Siegfried; et al.
Abstract : Objectives. Only few studies investigated treatment strategies for treatment resistant depression (TRD). The objective of this multicentre study was to evaluate TRD patients who did not respond to at least two antidepressants. Methods. A total of 417 patients, who failed to respond to a previous retrospectively assessed antidepressant (AD1), were firstly included in a 6-week venlafaxine treatment (AD2); secondly, those who failed to respond were treated for further 6 weeks with escitalopram (AD3). Results. Out of 417 patients who had failed to respond to previous treatment (AD1), 334 completed treatment with venlafaxine to prospectively define TRD. In the intent to treat (ITT) population in the first phase of the trial (AD2), responders to venlafaxine were 151 (36.21%) out of which remitters were 83 (19.90%). After phase one, 170 non-responders, defined as TRD, were included in the second phase and 157 completed the course. Of the 170 ITT entering the second phase (AD3), responders to escitalopram were 71 (41.76%) out of which remitters were 39 (22.94%). After the third treatment, patients showed a dropout rate of 7.65% and a rate of presence of at least one serious adverse event of 19.18%. Conclusions. Relevant rates of response and remission may be observed after a third line treatment in patients resistant to two previous treatments. A relevant limitation of this study was represented by the design: naturalistic, non-randomized, open-label, without a control sample and with unblinded raters.